Spiritualitas Kemiskinan Imam Diosesan di Tengah Tantangan Masa Kini - Karyanto, Andrian Widi (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2021)
In Catholicity, one of the Gospel values integrated in the formation of a priest is the spirituality of poverty. A diocesan priest also needs to live the spirituality of poverty as a way of life by living a simple and modest life. Today, however, on the one hand the spirituality of poverty is less considered as a requirement of a priestly way of life. On the other hand, living a simple life becomes more of a witness to the world that is constantly influenced by consumerism. In daily life, a priest must commit himself fully to the ministry, without expecting anything in return. An honest and total service of the priest will form a required personal quality that is realised in the three priestly duties, that is, as “priest, king, and prophet”. When reflected on in the vocational life of a diocesan priest, the spirituality of poverty will need to be explored further in face of the many challenges existing in the world today. Seeing the different perspectives of this spirituality, even if its is not considered as a requirement for the diocesan priest, might bring the inner potentials of this way of life to the surface.